Tecnologia e sociedade: o caso SIVAM - Rossi, Isabel Cristina (Universidade Federal de São Carlos, 2011)
The main purpose of this thesis is to approach the Sistema de Vigilância da Amazônia [Amazônia Vigilance System, SIVAM] as part of the military strategy for establishing Brazil as a power/leadership in South America. Because this strategy Brazil had to pay a high price for the world superpower asset and, by this way, the Brazilian militaries kept in force their politic power, their status quo, remains of the dictatorship era in face of a civilian regime. The referred asset can be realized as in effect since the very moment of the Air Force Department establishment, which happened at the same time of the creation of the Brazilian Air Force (FAB) during the Second World War and its research institutes Air Force Technology Institute (ITA) and Air Force Technology Center (CTA) , which had the purpose to raise and prepare critical mass for the later development of aeronautics. By the end of the Second World War Brazil dismantled its small, although important, aeronautics industry, which had many years of experience in aircraft construction. All the researches and experience were thrown away because lack of investments in this industry, result of the Brazilian government option for buying the French and American war leftovers . National interests were put aside with this attitude because the alignment with the United States would provide access to power and reputation for the Brazilian military elite, reason why it was essential to turn the country into a sub-hegemonic power in South America. It happened a similar process with the SIVAM when it was bought technology for its project and not used technology that could be developed inwards by Brazil. Brazilian militaries established the SIVAM with a nationalistic speech that had in its terms the preservation of the sovereignty and defense of the national territory. However, the praxis was contradictory since it revealed authentic the critics made against the SIVAM as an inefficient and outmoded system during its development. This study intends to make considerations in order to offer a possible explication for this attitude onto the specific case of the SIVAM.
Keywords: Sub-hegemonia; Teoria da dependência; Relações internacionais; Militarismo; Amazonia; SIVAM; Ciência e tecnologia; SIVAM; Sub-hegemony; Theory of dependency; International relations; Militarism; Science and technology; CIENCIAS HUMANAS::CIENCIA POLITICA